RSV infection of humanized lung-only mice induces pathological changes resembling severe bronchiolitis and bronchopneumonia - De, Chandrav; Pickles, Raymond J.; Yao, Wenbo; Liao, Baolin; Boone, Allison; Cleary, Rachel A.; Garcia, J. Victor; Wahl, Angela (Frontiers in Virology, 2024)
Respiratory syncytial virus (RSV) is a substantial cause of severe lower respiratory tract infections in infants, young children, older adults, and immunocompromised individuals. There is a vital need for effective therapeutics to prevent and/or treat severe RSV infection in these high-risk individuals. The development and pre-clinical testing of candidate RSV therapeutics could be accelerated by their evaluation in animals models that recapitulate bronchiolitis and bronchopneumonia; both hallmark features of severe RSV infection of humans. Previously, we demonstrated that implanted human lung tissue in humanized lung-only mice (LoM) can be infected with RSV resulting in a sustained virus replication. Here, we analyzed RSV-associated human lung pathology in the human lung implants of RSV-infected LoM. RSV infected epithelial cells lining the airway and alveolar regions of human lung implants resulting in hallmark histological features of RSV bronchiolitis and bronchopneumonia including distal airway and alveolar lumens clogged with 1) sloughed and necrotic RSV-infected epithelial cells, 2) neutrophil-containing inflammatory infiltrates, and 3) MUC5B dominated mucus secretions.We also show that treatment of LoM with a small molecule antiviral (ribavirin) or a neutralizing antibody (palivizumab) significantly suppressed and/or prevented RSV infection in vivo.Together, our data show that RSV infection of human lung implants in vivo has appropriate cellular tropism and results in hallmark pathological characteristics of severe bronchiolitis and bronchopneumonia in humans. They also offer proof-of-principle of the utility of this model to evaluate novel approaches for the prevention/treatment of RSV infection.